Management of Program Plus Curriculum Development In Madrasah Ibtidaiyah - Ayep Rosidi (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
T The research described the management of curriculum development in MI Suruh 01 Plus. The study used a qualitative approach. The data was collected through observation, in-depth interviews, and documentation. The data analysis was done by giving meaning to the collected information, and the conclusion was directed from the meaning. The research showed that the management of curriculum development plus program in MI Suruh 01 plus was conducted through four phases; 1) planning, concerning the principal and the primary curriculum development, then organized through work assembly. 2) Organizing; involved organizing the teachers and organizing learning material. 3) Actuating; involved improving human resources (teachers and school staff), cooperation, holding Education, the culture of discipline worship, methods and evaluation of learning result and, 4) Evaluating, involved input evaluation, process evaluation, and output evaluation.